MiR-103 protects from recurrent spontaneous abortion via inhibiting STAT1 mediated M1 macrophage polarization - Zhu, Xiaoxiao; Liu, Haiping; Zhang, Zhen; Wei, Ran; Zhou, Xianbin; Wang, Zhaoxia; Zhao, Lin; Guo, Qiang; Zhang, Yunhong; Chu, Chu; Wang, Li; Li, Xia (International journal of biological sciences, 2020)
Recurrent spontaneous abortion (RSA) is a common complication of early pregnancy. Excessive M1 macrophage was found to be involved in RSA, but the underlying mechanisms remains unclear. MicroRNAs play critical roles in RSA as well as the polarization of macrophages; however, the regulatory effect of miRNAs on M1 differentiation in RSA has not been fully investigated. In this study, miRNA microarray assay revealed that miR-103 was significantly decreased in RAW264.7-derived M1 macrophages upon IFNγ and LPS stimulation. Quantitative real-time polymerase chain reaction (qRT-PCR) analysis showed that in RSA patients, miR-103 expression was decreased substantially, and negatively correlated with that of STAT1. Moreover, down-regulation of miR-103 could sensitively discriminate RSA patients from normal pregnancies (NP) subjects. Experiments showed that overexpression of miR-103 suppressed M1 polarization by inhibiting STAT1/IRF1 signaling pathway and vice versa. miR-103 regulated STAT1 expression by direct binding to its 3'-UTR. Moreover, our study demonstrated that overexpressed miR-103 could reduce mice embryo resorption and M1 polarization effectively. Overall, the results suggested that decreased miR-103 was involved in RSA by increasing M1 macrophage polarization via promoting STAT1/IRF1 signaling pathway. miR-103 may be explored as a promising diagnostic marker and therapeutic target for RSA.